Thermo-Rheological Properties of the Ethiopian Lithosphere and Evidence for Transient Fluid Induced Lower Crustal Seismicity Beneath the Ethiopian Rift - Ameha A. Muluneh; Derek Keir; Derek Keir; Giacomo Corti (Frontiers in Earth Science, 2021)
Lower crustal earthquakes at plate boundaries and intraplate settings occur at depth where deformation is normally expected to occur in a ductile manner. Here we use the available earthquake catalogs and compute theoretical predictions for a range of conditions for the occurrence of lower crustal earthquakes beneath the Main Ethiopian Rift (MER) and adjacent north-western (NW) plateau. Yield strength envelops are constructed using information on geothermal gradient, strain rate, and composition constrained by geophysical observations. Our models suggest that away from the MER beneath the NW plateau the depth distribution of earthquakes in the lower crust is best explained by strong mafic lower crustal rheology and hydrostatic fluid pore pressure conditions. In the same region the effective elastic thickness is similar to seismogenic thickness showing that the lower crust has long-term strength and hence can physically support brittle deformation. On the contrary, in the central MER the seismogenic thickness is much larger than the effective elastic layer thickness implying that the lower crust has no long-term strength. Here our models show that both hydrostatic and near-lithostatic fluid pore pressures fail to explain the observed seismicity and instead a combination of near-lithostatic pore fluid pressure and transient high strain rate due to the movement of fluids provide a plausible mechanism for the occurrence of seismicity in the lower crust. Our interpretations are supported by occurrence of swarms of deep earthquakes beneath the MER, as opposed to more continuous background deep seismicity away from the rift. Using time-depth progression of earthquakes, we estimate permeability values of 5.9 × 10−15 m2 and 1.8 × 10−14 m2 at lower crustal depth. The range of permeability implies that seismicity can be induced by pore-pressure diffusion, likely from fluids sourced from the mantle that reactivate preexisting faults in the lower crust. Our thermo-rheological models explain the first order differences in lower crustal earthquakes both directly beneath and outboard of the rift valley.